New stories on the European Union's democratic deficit - Kyrieri, Katerina-Marina (2002)
The term 'democratic deficit' often masks an unjustified presupposition that the EU should follow similar democratic practices to those found in national arenas. Attempts to replicate national democratic Institutions tend to lead to unsatisfactory solutions at the EU level. A legitimate and democratic Union may involve innovations for which there are no precedents in national experiences of democratic politics.